A dopamine modified Li6.4La3Zr1.4Ta0.6O12/PEO solid-state electrolyte: enhanced thermal and electrochemical properties. Issue 27 (26th June 2019) - Huang, Zeya; Pang, Wanying; Liang, Peng; Jin, Zhehui; Grundish, Nicholas; Li, Yutao; Wang, Chang-An
Abstract : A garnet-type solid-state electrolyte Li6.4 La3 Zr1.4 Ta0.6 O12 (LLZTO) was modified using dopamine to improve the wettability of LLZTO with PEO, allowing 80 wt% LLZTO to be uniformly dispersed in 20 wt% PEO/LiTFSI polymer electrolyte. Abstract : A garnet-type solid-state electrolyte Li6.4 La3 Zr1.4 Ta0.6 O12 (LLZTO) was modified using dopamine to improve the wettability of LLZTO with PEO, allowing 80 wt% LLZTO to be uniformly dispersed in 20 wt% PEO/LiTFSI polymer electrolyte. Transmission electron microscopy and Fourier transform infrared spectroscopy confirmed a 4–5 nm thick polydopamine (PDA) layer coating on LLZTO nanoparticles. The composite LLZTO@PDA/PEO electrolyte was synthesized using a solvent casting method. The composite electrolyte has good compatibility and adhesion with both positive and negative electrodes of Li-ion batteries owing to the superior wetting capability of dopamine. This property allows for improved interfacial contact at the electrode/solid electrolyte interface which can decrease the overall resistance of the battery. With dopamine modification, the conductivity of the composite electrolyte at 30 °C increased from 6.3 × 10 −5 S cm −1 to 1.1 × 10 −4 S cm −1, and the interfacial resistance between the composite electrolyte and a metallic lithium anode decreased from 308 Ω cm 2 to 65 Ω cm 2 at 50 °C. The composite electrolyte also demonstrated improved thermal stability.